2013
DOI: 10.1080/14786419.2012.665911
|View full text |Cite
|
Sign up to set email alerts
|

Structure elucidation of a new natural diketopiperazine from aMicrobispora aeratastrain isolated from Livingston Island, Antarctica

Abstract: A new natural diketopiperazine (1) was obtained from the culture broth of Microbispora aerata strain imbas-11A, isolated from penguin excrements collected on the Antarctic Livingston Island. Compound 1 was purified consecutively by solvent extraction, silica gel column chromatography and preparative HPLC. The structure of the compound was elucidated by 1D and 2D NMR experiments and mass spectrometric investigations. The absolute configuration of compound 1 was determined by amino acid analysis and NOESY correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
10
0
3
Order By: Relevance
“…13). 88 Linfuranone A (288) is a new furanone-containing polyketide, which was discovered in a fermentation culture of Microbispora sp. GMKU 363 isolated from the root of a Thai medicinal plant (Clinacanthus siamensis Bremek.).…”
Section: Secondary Metabolites From Streptosporangiummentioning
confidence: 99%
See 1 more Smart Citation
“…13). 88 Linfuranone A (288) is a new furanone-containing polyketide, which was discovered in a fermentation culture of Microbispora sp. GMKU 363 isolated from the root of a Thai medicinal plant (Clinacanthus siamensis Bremek.).…”
Section: Secondary Metabolites From Streptosporangiummentioning
confidence: 99%
“…2EPS was isolated. The strain produced three known 26 A previously undescribed g-pyrone, miaolienone (79), and a new butanolide, miaolinolide (80), along with 13 known compounds (81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93), were obtained from Actinomadura miaoliensis BCRC 16873, which was isolated from a soil sample collected in Miaoli County, Taiwan. Compounds 79 and 80 could inhibit the production of TNF-a in U937 cells in vitro signicantly, and the IC 50 values were 0.59 and 0.76 mM, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…They are extensively obtained by extraction from natural sources, but may be easily synthesised. For both natural and synthetic diketopiperazines, a wide variety of biological activities was reported, including antitumour, antiviral, antifungal and antibacterial activities (Ivanova et al 2013). In recent years, the antifouling activities of the diketopiperazines had been studied.…”
Section: Resultsmentioning
confidence: 99%
“…Diketopiperazines present biological activities such as antiviral, antifungal, antibacterial, insecticidal, antihyperglycemic agents, receptor affinities of calcium channels and serotonergic [19][20][21] . Recent studies have demonstrated that diketopiperazine trans-cyclo(D-tryptophanyl-L-tyrosyl) presented low antiproliferative and cytotoxic effect with L-929 mouse fibroblast cells, K-562 leukemia cells and human HeLa Human cervix carcinoma 22 . Several arylethylamides present phytotoxic potential 23 .…”
Section: Introductionmentioning
confidence: 99%